2000
DOI: 10.1897/1551-5028(2000)019<0962:aipcai>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Prey Capture and Induction of Metallothioneins in Grass Shrimp Fed Cadmium-Contaminated Prey

Abstract: Abstract-The aquatic oligochaete Limnodrilus hoffmeisteri from a Cd-contaminated cove on the Hudson River, Foundry Cove, New York, USA, has evolved Cd resistance. Past studies have focused on how the mode of detoxification of Cd by these Cdresistant worms influences Cd trophic transfer to the grass shrimp Palaemonetes pugio. In the present study, we investigate reductions in prey capture in grass shrimp fed Cd-contaminated prey. We also investigate the induction of metal-binding proteins, metallothioneins, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…1C). The process of reversal of resistance, therefore, has had a potential large-scale ecological effect because resistant genotypes transfer Cd more efficiently through the food web (17) and affect both the Cd concentrations and prey-location ability of predators (27).…”
Section: Discussionmentioning
confidence: 99%
“…1C). The process of reversal of resistance, therefore, has had a potential large-scale ecological effect because resistant genotypes transfer Cd more efficiently through the food web (17) and affect both the Cd concentrations and prey-location ability of predators (27).…”
Section: Discussionmentioning
confidence: 99%
“…During Cd uptake, the BDM-Cd fraction may serve as the primary mechanism of detoxification. However, the system may become overwhelmed and Cd may bind to more sensitive cellular components (MSF), resulting in toxicity during a period of higher Cd exposure (Wallace et al, 2000). Wang and Wang (2008) suggested that the MSF-Cd best predicted Cd toxicity in marine diatoms under different environmental conditions.…”
Section: Subcellular Distributionmentioning
confidence: 99%
“…Nevertheless, in many intensely polluted areas, no annelids persist because the concentration of toxicants is too high to detoxify (Steichen et al 1996). In contrast, there are relatively fewer species of arthropods and echinoderms with opportunistic life histories, and these phyla are more sensitive to toxic chemicals because they generally lack detoxification mechanisms (James 1989, Bryan & Langston 1992, but see Nassir et al 2000, Wallace et al 2000. In sediments with high organic loading, very few macroorganisms persist in any phylum because of high microbial oxygen demand leading to hypoxia/anoxia and the production of toxic hydrogen sulfide (Fenchel & Riedl 1970, Pearson & Rosenberg 1978, Diaz & Rosenberg 1995.…”
Section: Life History Traits Of Marine Benthic Invertebratesmentioning
confidence: 99%